Особливості страхування майбутнього урожаю зернових культур за програмою форвардних закупівель - Рубцова, Наталя Миколаївна; Рубцова, Наталья Николаевна; Rubtsova, Natalia; Захарова, Наталя Юріївна; Захарова, Наталья Юрьевна; Zakharova, Natalia (My University, 2018)
UK: Вивчено порядок укладання форвардних контрактів на поставку зерна майбутнього урожаю. Охарактеризовані компанії, які здійснюють форвардні закупівлі майбутнього врожаю сільськогосподарських культур. Визначено перелік страхових компаній, які мають ліцензію на страхування сільськогосподарської продукції. Наведені основні умови договорів страхування посівів й майбутнього урожаю сільськогосподарських культур та здійснено приклад розрахунків за основними показниками. Представлено схему укладання договорів агрострахування за умовами форвардного контракту без / з державною підтримкою. EN: It has been determined that the state has developed a number of programs for the development of agriculture, in particular a forward-looking program of state support for agricultural producers, to ensure the food security of our country. Characterized companies that carry forward purchases of future crops. The order of conclusion of forward contracts for the supply of grain of the future harvest is explored. It was established that when entering into forward contracts for the supply of grain of the future harvest, the acquisition of a comprehensive insurance contract for future crop yields is a prerequisite. The list of insurance companies, which have a license for agricultural products insurance and actively work in the insurance market, is determined. The basic indexes of insurance, connected with the state pro-grams of financing of the agricultural producers are analyzed. The basic conditions of contracts of insurance of crops and the future crop of crops are given and an example of calculations according to the main indicators is made. The main provisions of the draft Law of Ukraine "On state support for agricultural insurance" are considered, which provides for an adjusted mechanism for subsidies to reduce insurance premiums to agricultural producers in the conclusion of a contract of agricultural insurance. The scheme (procedure) of conclusion of insurance contracts of agricultural crops under conditions of a forward contract without / with state support is presented. The choice of the optimal in-surance contract at the conclusion of a forward contract is made.
Features of future increasing grain cultures insurance by the forwarding purchase program
Keywords: сільськогосподарське виробництво; форвардний контракт; агрострахування; страхові компанії; договір страхування; стандартні страхові продукти; державна підтримка; agricultural production; forward contract; agri-insurance; insurance companies; insurance contract; standard insurance products; state support